(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
As a result of the resarches in Armenia there have been found 92 species belonging to genus Ascochyta. In the list included in the article besides the latin names of the species there are also pointed the authors, the names of the host plants, the places of collection and the dates.